Precision wavelength measurement of the 14.4 keV Mössbauer photon - Xiaowei, Z (Journal of synchrotron radiation, 2000)
The wavelength of the 14.4 keV Mössbauer photon has been determined by using undulator radiation and diffraction of FZ silicon crystals. For the wavelength determination a goniometer equipped with a laser rotary encoder and a sine-bar angle optical interferometer was developed; a temperature-monitoring system and X-ray optics related to the experiment were also developed. The mean wavelength was 0.08602557 nm with an uncertainty of 0.6 p.p.m., derived from 16 measurements of three pieces of FZ Si(840) crystals